What is Market: Socio-Economic Approach - РадаевВадим Валерьевич (Journal of Economic Sociology, 2010)
This paper focuses on the term of market and suggests a non-traditional variant of its consideration from the point of view of market sociology as the leading field of contemporary economic sociology. The proposed approach is not against or instead of the contemporary economic theory. The approach suggests new additional variants that let us discuss the current markets under new conditions.